Molecular epidemiology of Mycobacterium tuberculosis in Nepal. - Malla, Bijaya (2013)
SUMMARY: Tuberculosis (TB) is a global health problem. One reason of conducting molecular epidemiology studies is to understand the uneven distribution of the disease in different parts of the world. The global population structure of MTBC can be studied by genotyping strains from different geographic regions, which describes the evolutionary relatedness of MTBC. The choice of appropriate genetic tools is fundamental that can elucidate local as well as global spread of disease. Genetic markers like large sequence polymorphisms (LSPs) and single nucleotide polymorphisms (SNPs) have been used to construct phylogenies of MTBC lineages that are informative for understanding the global distribution of MTBC. Additionally, markers such as direct repeats can differentiate strains within smaller geographical settings or cohort of patients. Studies have shown that the lineages diversity itself could be associated with differences in the pathogenesis and epidemiology of TB. Most importantly, the emergence of drug resistance, which results mostly among treatment failures, is a serious threat to TB control programs. Our aim was to use those markers to explore the phylogenetic diversity and distribution of MTBC in Nepal and compare it to the global phylogeography of MTBC. Furthermore, to identify the mutational hotspots conferring drug resistance. Understanding the molecular mechanisms of drug resistance will allow us to develop rapid molecular drug resistance detection tools and management of TB cases with improved and more rational drug therapies. We used SNPs based genotyping tool for 506 M. tuberculosis strains from Nepal. This revealed four major lineages of MTBC. This allowed us to map the MTBC structure in Nepal compared to the global diversity. Additionally, the use of spoligotyping and MIRU-VNTR (used for XDR strains only) provided data within particular geographical settings and within human populations. A total of 69 different spoligotypes with unique SIT numbers were identified. We found Beijing and Central Asian Strain (CAS) family as the predominant genotypes as was expected owing to geo-position of Nepal in Asia. Molecular analysis of drug resistance for most common anti-TB drugs (i.e. isoniazid, rifampicin) from our sample set confirmed that the polymorphisms were more or less similar as previously documented globally, although we found some additional non-synonymous mutations which need validation. In general, our findings showed that the rapid molecular tools currently developed will detect most of the drug resistance isolates in Nepal. Among drug resistance strains, the katG S315T was proportionally more represented by multi-drug resistance strains. However, the patterns of rpoB mutation were unrelated to multi-drug resistance or MTBC genotypes. By performing 24 MIRU-VNTR loci plus additional 4 hyper variable region intended to use for Beijing spoligotypes, we provide evidence of primary transmission of XDR strains. On the other hand, the aim was to identify risk factors, risk groups, and co-morbidities that may relate to the susceptibility to TB. The number of male patients constituted two-third of the total sample population and most of them were at the age of 15-24 years. However, female TB patients in Nepal seem to be associated with "virulent" strains of TB (Beijing genotype) and drug resistance. We identified four XDR cases; the younger age (median age 21 yrs.) of XDR-TB is a serious matter that requires immediate attention from NTP, Nepal.